HUBUNGAN KETERATURAN MENGIKUTI SENAM LANSIA DENGAN KUALITAS HIDUP LANSIA - Ernofi " "; Bayhakki " "; Sri " Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Elderly gymnastics  is a series of  regular motion and directional also have been planned that done  individually or in groups with the purpose to increase the body functional abilities for achieving these objectives. Quality of life is a state perceived to the patient’s condition appropriate to the cultural context and value system that trusted,including purpose of life. This research purpose was to know the relationship of regularity following elderly Gymnastics with Elderly Quality of Life in Posyandu of Elderly of Bumi Ayu Village with the correlation descriptive research design and cross sectional approach. The sample were 89 respondents that taken according to the inclusion criteria using purpose sampling technique. Measuring instrument that used were Questionnaire of Regularity Following Elderly Gymnastics and Questionnaire of World Health Organization of Quality of Life (WHOQOL).The Univariate Analysis to show the distribution frequency and Bivariate Analysis using Chi Square Test. The result showed that there is a relationship of regularity following elderly gymnastics witch elderly quality of life,with p value (0,007). The results of this research is recommended for health workers especially nurse to increase the elderly motivation in following elderly gymnastics.